COVID 19 PANDEMIC AND THE IMPACT ON DENTISTRY PRACTICE. OPINION OF UNIVERSITY TEACHERS - Liana Todor; Magdalena Iorga; Beatrice-Gabriela Ioan (Romanian Society of Oral Rehabilitation, 2020)
The aim of the study is to identify the opinion of academics regarding the new practices in dentistry clinicals environment Material and methods: the study was conducted in a single university center; an online questionnaire was distributed among teachers in a dentistry faculty. In total, 23 doctors (74.19% of the teaching staff) were included in the research. The items were constructed especially for this study and gathered socio-demographic and medical data, information about practices in the new pandemic conditions, job-related aspects and self-rated fear of being infected with COVID 19 or transmitting to the family members. Data were processed using SPSS, version 23. Results: most participants are women; the average of dentists is 40.57 ± 8.33 years old with a length of experience in the dentistry field of 15.33 ± 8.52 years. 26% of doctors have had no free days in the last eight months. A total of 82.60% of doctors plan the consultations, 56.50% practice always have telephonic triage, 78.30% always ask patients to complete the triage form and 39.10% of doctors schedule consultation according to the severity of the dental condition. 87% provide additional protective measures when they provide medical care to patients. Conclusion: Dental health care personnel need to understand the implications of potential transmission of the virus in a clinical setup and must respect guidelines to diminish the risk of infection.